The protectorate of Russia over Tuva in 1914–1925 (an historic and legal aspect) - Mollerov, Nikolay M. (The New Research of Tuva, 2014)
Article presents the author’s presentation at International Science Conference devoted to 100th jubilee "United Tuva in united Russia: history, modernity, futures” (July 3-4, 2014, Kyzyl).Questions of the relevance of protectorate in the past and at modernity, the legitimization of the actions directed to the protectorate’s establishment, and the legal status of the protectorate are considered. Noted are the legal collisions related to the revocation and preservation of the protectorate in 1917-1925.